Jiang, Q.Q., Deng, H.P., Wang, Q., Yang, Z.M. & Zhang, H.Y. (2017) Clematis wuxiensis (Ranunculaceae), a new species from Chongqing, China. Phytotaxa 296 (2): 197–200 - Jiang, Qing-Qing; Deng, Hong-Ping; Wang, Qian; Yang, Zhi-Ming; Zhang, Hua-Yu (Phytotaxa, 2017)
N/A